Advanced Chunking Techniques: a Novel Approach for Semantic Splitters - Ramos Toresan, Bernardo; Pereira Moreira, Viviane; Soares Fagundes Paula, Felipe; Regina Bencke, Luciana (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2025.247263, 2025)
Chunking, the process of splitting large amounts of text into processable parts, is an essential but often overlooked step for multiple Information Retrieval and Vector Databases tasks. Traditional chunking techniques rely on fixed-length or syntactic structures, creating opportunities for more meaningful approaches. Semantic chunking is the process of dividing text based on meaning and context, ensuring each chunk represents a logical unit of information. This work proposes the Dual Semantic Chunker, which represents an advancement over existing chunking methods by taking a closer look at semantic representation. We compared multiple chunking methods, including both semantic and traditional techniques, and achieved improved retrieval.